Phagocytosis is coupled to the formation of phagosome-associated podosomes and a transient disruption of podosomes in human macrophages - Margot Tertrais; Claire Bigot; Emmanuel Martin; Renaud Poincloux; Arnaud Labrousse; Isabelle Maridonneau-Parini (European Journal of Cell Biology, 2021)
Phagocytosis consists in ingestion and digestion of large particles, a process strictly dependent on actin re-organization. Using synchronized phagocytosis of IgG-coated latex beads (IgG-LB), zymosan or serum opsonized-zymosan, we report the formation of actin structures on both phagocytic cups and closed phagosomes in human macrophages. Their lifespan, size, protein composition and organization are similar to podosomes. Thus, we called these actin structures phagosome-associated podosomes (PAPs). Concomitantly to the formation of PAPs, a transient disruption of podosomes occurred at the ventral face of macrophages. Similarly to podosomes, which are targeted by vesicles containing proteases, the presence of PAPs correlated with the maturation of phagosomes into phagolysosomes. The ingestion of LB without IgG did not trigger PAPs formation, did not lead to podosome disruption and maturation to phagolysosomes, suggesting that these events are linked together. Although similar to podosomes, we found that PAPs differed by being resistant to the Arp2/3 inhibitor CK666. Thus, we describe a podosome subtype which forms on phagosomes where it probably serves several tasks of this multifunctional structure.